0238 Campus Food Pantry Assistance is Related to Better Physical And Mental Health Through Adequate Sleep Among College Students in a Public University System. (27th May 2020) - Martinez, S; Kalaydjian, S; Ritchie, L; Nazmi, A; Prather, A
Abstract: Introduction: Food insecurity is an issue among students in higher education and has been linked to insufficient sleep, and poor mental and general health. College campuses have quickly responded by establishing campus food pantries. However, the extent to which campus food pantries are ameliorating the impacts of food insecurity is unknown. Methods: Online survey data were collected from a cross-sectional sample of 1, 855 students who were food pantry users in the 10-campus UC system. Students were asked to report their number of visits to a food pantry in the past month, and to rate their general health, depressive symptoms, and number of days of enough sleep (in a week) before and after food pantry access. Changes in days of enough sleep, depressive symptoms and general health were computed. Demographic characteristics were obtained from institutional data. Path analysis was used to examine direct and indirect pathways from food pantry use to depressive symptoms and general health through enough sleep days, controlling for workstudy receipt, Pell grant receipt and family income. Results: Students on average were 21.7 years old (SD= 3.5), and had more days of adequate sleep (25%), and improved depressive symptoms (43%) and general health (31%) after obtaining services from a campus food pantry. An increase in monthly food pantry use was directly related to a decrease in depressive symptoms (β= 0.08, p<0.001) and an increase in general health (β= 0.07, p=0.001). Additionally, an increase in food pantry use related to an increase in getting more days of enough sleep (β=0.07, p=0.001), which in turn positively related to a decrease in depressive symptoms (β=0.18, p<0.001) and improved general health (β=0.24, p<0.001). Conclusion: Food pantry use had a positive relationship with student health outcomes, and enough sleep days played an important mediating role. Findings suggest that emergency food access may have a positive impact on student health outcomes. Support: This study was funded by the UC Campus Basic Needs Committees.